Peaceful (But Not Passive) Resistance to Empire: Maximus the Confessor and the Politeia of Jesus Christ - Blowers, Paul M. (Modern theology, 2025)
During the Monothelete Controversy, the last phase of the ancient Christological controversies engaging Eastern and Western churches in the seventh century, the Byzantine monastic theologian Maximus the Confessor not only developed a crucial defense of the dual (divine and human) wills in Jesus Christ, he also mounted a broad monastic and ecclesiastical dissent from the doctrinal positions of the imperial establishment. Establishing the cultural and theological context of his career, this essay explores the extent to which Maximus's Christocentric cosmology and eschatology, combined with his own activism and networks of relationships, rose to the level of a serious “political” challenge to Byzantine imperial aspirations. The ultimate focus is on Maximus's principle of the politeia of Jesus Christ, the new way of life inaugurated by Christ, to which all rational creatures are called to conform precisely as a cruciform allegiance to the ruler of the universe whose government may intersect with earthly regimes but ultimately transcends and outlasts them.